Immunotherapy resistance in non-small-cell lung cancer: From mechanism to clinical strategies - Zhou, Suna; Yang, Haihua (Frontiers in Immunology, 2023)
The high primary resistance incidence and unavoidable secondary resistance are the major clinical obstacle to lasting long-term benefits in Non-small-cell lung cancer (NSCLC) patients treated with immunotherapy. The mechanisms of immunotherapy resistance in NSCLC are complex mainly involving tumor cells and tumor microenvironment (TME) infiltrating immune cells including TAMs, B cells, NK cells, and T cells. The selection of clinical strategies for NSCLC progression after immunotherapy resistance should be dependent on the progressive mode. The progressive mode in NSCLC patients after immunotherapy resistance can be summarized into oligo-progression and systemic/multiple progression, which should be taken into consideration for the selection of further treatment. In the future, it needs to explore how to optimize the combined therapy and explore strategies to reprogramme infiltrating immune cells under various genetic backgrounds of tumor cells and timely reshape TME during anti-tumor treatments.